The Role of Digital Technology in Facilitating Zakat Collection and Distribution in the Modern Era - Muhammad Musa Ali (ICO EDUSHA, 2024)
The development of digital technology in the modern era provides significant opportunities to increase the efficiency of zakat management, especially in the collection and distribution process. This research aims to identify the strategic role of digital technology in facilitating the zakat collection process, assess its effectiveness in increasing the speed and accuracy of distribution, and analyze the obstacles faced by zakat institutions in its implementation. The research approach used is descriptive qualitative with a case study method on several zakat institutions that have utilized digital platforms. Data was obtained through in-depth interviews, observations and documentation studies, which were then analyzed to provide a comprehensive picture of the impact of digital technology on zakat management. The research results show that digital technology is able to simplify the zakat collection process through various online payment options and increase distribution efficiency with real-time integrated data, which enables faster and more targeted distribution. However, obstacles such as people's low digital literacy and risks related to data security are still obstacles in implementing this digital technology. The conclusion of this research confirms that digital technology plays an important role in efforts to modernize zakat management, with great potential in increasing efficiency and transparency. The main recommendation given is the importance of increasing digital education for the public and developing adequate digital infrastructure to support more optimal implementation of technology in managing zakat in the future. Keywords: Efficiency of zakat management in the modern era